The effects of socio-political context on tourism - Shahrabani, S.; Teitler-Regev, S.; Syna, H. D.; Tsoukatos, E.; Ambrosio, V.; Loureiro, S. M. C.; Voulgaris, F. (EuroMed Journal of Business, 2019)
Purpose: The purpose of this paper is to examine the effects of tourists’ perceptions of political and economic instability and risks of terrorism on their intentions to travel to countries associated with various risks. Design/methodology/approach: A total of 648 Greek, Israeli and Portuguese students completed a questionnaire focusing on their perceptions concerning factors that shape their travel decisions. Findings: The findings showed that among tourists from Greece and Portugal, the experience of economic crisis and the salience of economic and political hardships mitigated their intentions to travel to destinations with similar problems. These factors had no effect on Israelis, who have not experienced such problems in their country. Frequent terrorist incidents diminished the intentions of Greek tourists to travel to destinations marked by terrorism, such as Israel. Thus, different factors affect tourists’ travel-related decisions in each of the three countries. Originality/value: The study sheds light on how potential tourists construe the risks of traveling to specific destination countries based on hazards in their home countries, a topic that to date has received little research attention.